ASSESSMENT MODEL OF HIGH SCHOOL STUDENTS' PERFORMANCE: EXPERIENCE OF UKRAINE - Olga Bilyakovska; Natalia Mospan; Kateryna Binytska (Borys Grinchenko Kyiv Metropolitan University, 2021)
The article considers modern approaches to assessment at schools based on the analysis of various assessment scales (range from three to one hundred points). The pedagogical regularities influencing the choice of assessment scales are determined, in particular: 1) increase of quantitative parameters of the assessment scale; 2) the use of a tribal rating scale for one-element answers; 3) the use of indirect evaluation with a significant amount of evaluation scale; 4) application of mathematical methods of transition from qualitative parameters to quantitative indicators of estimation; 5) taking into account the level of structure of the subject and the relationship between learning and development of subjects of study. Finally, we propose three secondary school testing and evaluation systems models that provide mathematical, humanities and general education. To identify the causal effects from different assessment scales, we conduct an educational experiment and a large-scale online survey in Ukrainian schools from 2019-2021. As a result of experimental research, we allocate the essential elements of testing and estimation activity: educational parameters, the structure of components of knowledge of a subject, criteria, a scale of estimations, an interval scale of transition to assessments, forms of final and local testing. The findings suggest that the developed approaches to assessing high school students' educational achievements are more effective than traditional ones. They encourage schoolchildren motivation to learn, in particular, in performing independent (especially homework) tasks. The obtained data confirm the need to use new approaches to assessing student achievement.